2011
DOI: 10.1590/s0100-29452011000300021
|View full text |Cite
|
Sign up to set email alerts
|

Similaridade genética entre acessos de goiabeiras e araçazeiros baseada em marcadores moleculares AFLP

Abstract: Espécies do gênero Psidium, como goiabeira e araçazeiros, são economicamente importantes e têm como área de diversidade genética primária o Brasil. Foram determinadas as relações genéticas, com base no marcador AFLP, para acessos do Banco Ativo de Germoplasma (BAG) de Psidium da Embrapa Semiárido, para orientar trabalhos de melhoramento e de manejo de recursos genéticos do gênero. Foram analisados 88 acessos, sendo 64 de goiabeira e 24 de araçazeiros, coletados em dez Estados brasileiros, adotando-se para agru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
2
0
1
Order By: Relevance
“…Rodríguez-Medina et al (2010) found similarity ranging from 0.40 to 1.00 among 43 accessions of a Cuban guava collection, which was evaluated using 7 microsatellite markers. High genetic variability was also found and reported by Corrêa et al (2011) for 88 Psidium accessions of the same collection, evaluated using AFLP markers. The 183 alleles of the 13 microsatellites were sufficient to separate the guava accessions from araçazeiro accessions.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Rodríguez-Medina et al (2010) found similarity ranging from 0.40 to 1.00 among 43 accessions of a Cuban guava collection, which was evaluated using 7 microsatellite markers. High genetic variability was also found and reported by Corrêa et al (2011) for 88 Psidium accessions of the same collection, evaluated using AFLP markers. The 183 alleles of the 13 microsatellites were sufficient to separate the guava accessions from araçazeiro accessions.…”
Section: Resultssupporting
confidence: 72%
“…However, this marker has a low reproducibility and is dominant (Esselink et al, 2003). Corrêa et al (2011) studied and compared the genetic similarity of 62 guava and 24 araçazeiro accessions by using amplified fragment length polymorphism (AFLP) markers and separated the genotypes into 2 groups, one formed by guava accessions and another by araçazeiro accessions with the inclusion of some guava accessions, with a similarity ranging from 28 to 98%. -Infante et al (2007) were the first to report and characterize Cuban guava accessions by using microsatellites.…”
Section: Introductionmentioning
confidence: 99%
“…Corrêa et al (2011), avaliando a similaridade genética com a utilização de AFLP, obtiveram a formação de diferentes agrupamentos em acessos de goiaba coletados em diferentes regiões do Brasil. Sanabria et al (2006), com a utilização de 74 marcadores polimórficos de RAPD, reportaram também alta diferenciação genética (0,355) entre 53 acessos de goiabeiras colombianas.…”
Section: Resultsunclassified
“…High genetic variability was also reported by da Costa and Santos (2013) among the 61 Psidium accessions of that same collection evaluated by microsatellite marker. Corrêa et al (2011) also reported high genetic variability among 88 Psidium accessions, with similarities ranging from 0.28 to 0.98 based on AFLP markers. These results indicate high discriminative power of SNP markers, even among genetically related materials when compared to results obtained with AFLP and SSR markers for the same collection of accessions.…”
Section: Similarity Genetic Based On Dendrogram Of Jaccard Coefficientmentioning
confidence: 91%